2019
DOI: 10.1364/oe.27.031176
|View full text |Cite
|
Sign up to set email alerts
|

Superradiant diamond color center arrays coupled to concave plasmonic nanoresonators

Abstract: authors equally contributed mcsete@physx.u-szeged.hu Different types of concave plasmonic nanoresonators have been optimized to achieve superradiantly enhanced emission of SiV color centers in diamond. Comparative study has been performed to consider advantages of different N number of SiV color centers, different diamond-silver (bare) and diamond-silver-diamond (coated) core-shell nanoresonator types, as well as of spherical and ellipsoidal geometry. The complete fluorescence enhancement (qualified by P x fac… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 46 publications
0
7
0
1
Order By: Relevance
“…Our previous studies have revealed that there is a trade-off between the total fluorescence enhancement ( P x factor , defined as the product of the radiative rate enhancements at the excitation ( δR ex ) and emission ( δR em )) and the antenna efficiency that is corrected with the intrinsic SiV color center quantum efficiency at the emission ( cQE ). These studies proved that optimization realized by using the objective function of P x and P x *cQE = P x × cQE product promotes to design efficient non-cooperative fluorescent and superradiant configurations, respectively [ 26 , 55 , 56 ]. Accordingly, we have selected the P x *cQE quantity as the objective function for the present numerical optimization.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our previous studies have revealed that there is a trade-off between the total fluorescence enhancement ( P x factor , defined as the product of the radiative rate enhancements at the excitation ( δR ex ) and emission ( δR em )) and the antenna efficiency that is corrected with the intrinsic SiV color center quantum efficiency at the emission ( cQE ). These studies proved that optimization realized by using the objective function of P x and P x *cQE = P x × cQE product promotes to design efficient non-cooperative fluorescent and superradiant configurations, respectively [ 26 , 55 , 56 ]. Accordingly, we have selected the P x *cQE quantity as the objective function for the present numerical optimization.…”
Section: Methodsmentioning
confidence: 99%
“…Accordingly, we have selected the P x *cQE quantity as the objective function for the present numerical optimization. The robustness of a method relying on this objective function is due to the relationship between the nanoresonator quality factor ( Q-factor that is proportional to the Purcell factor ) and superradiance, considering that bad-cavity characteristics allow it to achieve a maximal radiative rate, meaning on the level of superradiance [ 55 , 56 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 204 ] Supperradiance was experimentally demonstrated both with the NV and the SiV color centers. [ 270,271 ]…”
Section: Implementation and Materials For Quantum Antennasmentioning
confidence: 99%
“…Az ezüst nanorezonátorokkal a gerjesztés is erősíthető, ugyanakkor mindkét fém alkalmas az emisszió erősítésére. Az emisszió erősítése mellett az SiV színcentrum intrinsic kvantumhatásfokánál jobb hatékonyságot mutató csatolt emitter-nanorezonátor rendszerek is tervezhetők specifikus kvantuminformatikai célokra[3,4].2. ábra A vizsgált SNSPD rendszerekben az NbN/Au korrelációja az (a) NbN abszorpció és (b) polarizáció kontraszt értékekkel; (c) az integrált polarizációkontraszt értékek.…”
unclassified